A comparative analysis of substituting imported gas and coal for electricity with renewables – An input-output simulation. (December 2018) - Kamidelivand, Mitra; Cahill, Caiman; Llop, Maria; Rogan, Fionn; O'Gallachoir, Brian
Highlights: Extended I-O model to compare the socio-economic impacts of electricity scenarios. Techniques for disaggregating energy sectors, GHG emissions and employment numbers. Counting the lost jobs and value-added from energy and non-energy sectors. 26 net jobs and €5m net value-added for each 1% GHG reduction of gas substitution. 73–78% lower net jobs and net value-added for the coal substitution scenarios. Abstract: For many countries, the leading energy system decarbonisation strategy is to decrease reliance on imported fossil-fuel by developing renewable electricity. This paper offers insights on the net effects of transition to low fossil-based electricity by adapting an input-output (I-O) substitution model. Firstly, it addresses a common challenge with national I-O tables, namely how to isolate figures for inhomogeneous products like 'electricity' and 'gas' aggregated into one sector for a case study of Ireland. Secondly, it applies an extended I-O model to compare the net impacts on energy and non-energy sectors when substituting imported fossil fuels for electricity with renewable resources. Within the framework of the I-O model, for each 1% GHG reduction of the gas substitution scenario, there are increases of 26.2 net jobs and €5.1 m net value-added. These impacts are lower by 73–78% for coal substitution scenarios. Without taking account of the lost jobs and value-added from the economy, the job creations and value-added of renewable electricity would be overestimated by 17%–35% and 25%–50%, respectively. As well as giving insights into the net benefits of renewable electricity, the study provides techniques that could be applied to I-O tables for other jurisdictions to enable improved analysis of energy scenarios.